Response of the Cerebral Cortex to Resistance and Non-resistance Exercise Under Different Trajectories: A Functional Near-Infrared Spectroscopy Study - Shi, Ping; Li, Anan; Yu, Hongliu (Frontiers in Neuroscience, 2021)
Background: At present, the effect of upper limb movement is generally evaluated from the level of motor performance. The purpose of this study is to evaluate the response of cerebral cortex to different upper limb movement patterns from the perspective of neurophysiology. Method: 30 healthy adults (12 females, 18 males, mean age 23.9±0.9 years) took resistance and non-resistance exercises under four trajectories (T1: left and right straight-line movement; T2: front and back straight-line movement; T3: clockwise and anticlockwise drawing circle movement; T4: clockwise and anticlockwise character ❋ movement). Each movement included a set of periodic motions composed of a 30-seconds task and a 30-seconds rest. Functional near-infrared spectroscopy (fNIRS) was used to measure cerebral blood flow dynamics. Primary somatosensory cortex (S1), supplementary motor area (SMA), pre-motor area (PMA), primary motor cortex (M1) and dorsolateral prefrontal cortex (DLPFC) were chose as ROIs. Activation maps and symmetric heat maps were applied to assess the response of cerebral cortex to different motion patterns. Result: The activation of the brain cortex was significantly enhanced under resistance movement for each participant. Specifically, S1, SMA& PMA, and M1 had higher participation during both non-resistance movement and resistance movement. Compared to non-resistance movement, the resistance movement caused obvious response of cerebral cortex. The task state and the resting state were distinguished more obviously in the resistance movement. Four trajectories can be distinguished under non-resistance movement. Conclusion: This study confirmed that the response of cerebral motor cortex to different motion patterns was different from the neurophysiological level. It may provide reference for the evaluation of resistance training effect in the future.